Isometric Strength in Volleyball Players of Different Age: A Multidimensional Model - Majstorović, Nikola; Dopsaj, Milivoj; Grbić, Vladimir; Savić, Zoran; Vićentijević, Aleksandar; Aničić, Zdravko; Zadražnik, Marko; Toskić, Lazar; Nešić, Goran (Applied sciences, 2020)
Physical abilities modelling has a profound connection with long-term athlete development and talent identification. There is not enough data to support evidence about age-related changes in volleyball players’ isometric strength. This study aimed to define the age-related model of volleyball players multidimensional muscles’ contractile characteristics. The participants were divided according to gender (male n = 112, female n = 371) and according to age into four groups: under 15 (U15), under 17 (U17), under 19 (U19), and under 21 (U21) years old. Participants performed three isometric strength tests: handgrip, lumbar extensors, and ankle extensors. Maximal force and rate of force development results from all three tests were transformed into a single Score value as a representation of contractile potentials using principal component analysis. The main findings were that Score values of both genders showed significant differences between age groups (male: F = 53.17, p < 0.001; Female: F = 41.61, p < 0.001). Trends of those yearly changes were slightly more balanced for female subjects (3.9%) compared to male subjects (6.3%). These findings could help in strength training adjustments when working with volleyball players of a certain age, and enable coaches to detect ones that stand out positively, considering them as strong in regard to their age.